Rapid mold optimization based on ultraviolet curing 3D printing technology - Rao, Hanyu; Bai, Xinyu; Yan, Wen; Liu, Jie (Frontiers in Materials, 2025)
Injection molding is the most common method for making plastic products. However, quick molds made with ultraviolet (UV) curing 3D printing frequently employ photosensitive resins with low mechanical strength, rendering plastic components prone to warpage deformation. To solve this issue, our research focuses on the design and development of fast molds using UV-curing 3D printing technology. A response surface model was used to explore the effect of different process parameters on component warpage, with the goal of minimizing deformation. An upgraded particle swarm optimization (PSO) technique was then created to fine-tune the process parameters and reduce warpage even more. The results revealed that raising injection pressure, reducing temperature, and prolonging holding time successfully reduced warpage. During the single-peak Schwefel function test, the modified PSO method displayed greater optimization capabilities, achieving convergence in around 40 iterations. Using the modified values, the maximum warpage was lowered by 0.55 mm. Experimental results demonstrate the suggested optimization model’s performance, allowing for increased mold design flexibility and aiding the industry’s migration to digital and customized production.